Randomised trial of CPAP vs bilevel support in the treatment of obesity hypoventilation syndrome without severe nocturnal desaturation. Issue 5 (18th January 2008) - Piper, A J; Wang, D; Yee, B J; Barnes, D J; Grunstein, R R
Abstract : Background: Untreated, obesity hypoventilation is associated with significant use of health care resources and high mortality. It remains unclear whether continuous positive airway pressure (CPAP) or bilevel ventilatory support (BVS) should be used as initial management. The aim of this study was to determine if one form of positive pressure is superior to the other in improving daytime respiratory failure. Methods: A prospective randomised study was performed in patients with obesity hypoventilation referred with respiratory failure. After exclusion of patients with persisting severe nocturnal hypoxaemia (Spo 2 <80% for >10 min) or carbon dioxide retention (>10 mm Hg) despite optimal CPAP, the remaining patients were randomly assigned to receive either CPAP or BVS over a 3-month period. The primary outcome was change in daytime carbon dioxide level. Secondary outcome measures included daytime sleepiness, quality of life, compliance with treatment and psychomotor vigilance testing. Results: Thirty-six patients were randomised to either home CPAP (n = 18) or BVS (n = 18). The two groups did not differ significantly at baseline with regard to physiological or clinical characteristics. Following 3 months of treatment, daytime carbon dioxide levels decreased in both groups (CPAP 6 (8) mm Hg; BVS 7 (7) mm Hg) with no between-group differences. There was no difference in compliance between the two treatment groups (5.8 (2.4) h/night CPAP vs 6.1 (2.1) h/night BVS). Although both groups reported an improvement in daytime sleepiness, subjective sleep quality and psychomotor vigilance performance were better with BVS. Conclusions: Both CPAP and BVS appear to be equally effective in improving daytime hypercapnia in a subgroup of patients with obesity hypoventilation syndrome without severe nocturnal hypoxaemia. Trial registration number: Australian Clinical Trials Registry ACTRN01205000096651.